Inovasi Perawatan Kulit dengan Lulur dari Ampas Minuman Herbal - Nita, Nita; Srimularahmah, Andi; Asfar, Andi Muhammad Irfan Taufan; Asfar, Andi Muhamad Ikbal; Ahmad, Susiana; Arimbi, Arimbi (Unri Conference Series: Community Engagement, 2024)
Herbal drink dregs are the remaining natural ingredients left after the process of making herbal drinks. Although this dregs is usually considered waste, some people reuse it for other purposes such as Herb Scrub. The use of herbal drink dregs in Masago Village is not utilized due to lack of knowledge and skills of partners in processing herbal drink dregs. As a result, the community, especially the Taro Ada'E Karang Taruna Group in Masago Village, has not used the dregs of herbal drinks and tends to just throw them away. Therefore, this community service program aims to maximize the use of herbal drink dregs by processing them into a herbal scrub. This product has never been introduced by extension workers or other product innovations, especially in Bone Regency. Community empowerment through this service program is carried out through three main stages, namely counseling, training and mentoring. The results of this program show that partners are able to understand the benefits of processing herbal drink dregs and have the skills to turn them into a herbal scrub. Apart from that, partners have also succeeded in marketing products through the Marketplace with an increase in productivity of up to 99%. The impact of this service can realize sustainable development goals no. 3, namely a healthy and prosperous village.